The Run Off and Erosion on Eucalyptus Plantation Pt. Toba Pulp Lestari Aek Nauli Sector Simalungun District (International Journal of Scientific Research and Management (IJSRM), 2020)
This study aims to determine the amount of surface flow and the amount of erosion on vacant land and stands of Eucalyptus ages 1, 2, 3, 4 and 5 years in HTI PT. Toba Pulp Lestari, Aek Nauli sector. Observations dilakukan runoff and erosion measurements using runoff and erosion at each rain event system by observation of small plots measuring 22 x 4 m2 installed on each land cover circumstances. The state of each plot research is in the area of ​​vacant land, stands of age class 1, 2, 3, 4 and 5 years, with 9% slope. The number of plots a total of 6 plots. And surface flow measurement is done by measuring the volume of water in the drum. Observations magnitude of runoff and sedimentation performed every 2 months during rain events. The results showed that the surface flow field measurement results showed variation and change in vacant land and a variety of ages eucalyptus. Lowest runoff occurs in the plot of land cover Eucalyptus age 1 year and highest in plots of land cover Eucalyptus age 2 years. The highest erosion rates occurred in plots of vacant land and is followed by a decrease in the Age of Eucalyptus 1,2,3,4 and 5 years.